TRANSFORMASI MANAJEMEN KURIKULUM PESANTREN MENUJU STANDAR PENDIDIKAN NASIONAL - Moch. Mahdiyan Nasikhin; Ali Fajri (Universitas Islam Bunga Bangsa Cirebon, 2024)
The pesantren, as Indonesia's oldest and most distinctive Islamic educational institution, stands at a critical crossroads between the imperative to preserve its classical tradition of Islamic scholarship and the growing pressure to align its curriculum management with national education standards. While the enactment of Law Number 18 of 2019 on Pesantren formally recognized pesantren as a distinct educational entity within the national system, the managerial transformation of pesantren curricula toward national standards remains a complex and largely underresearched process. This study investigates the transformation of pesantren curriculum management toward national education standards, pursuing three specific objectives: (1) to analyze the conceptual tensions between pesantren's traditional curriculum paradigm and national education standards requirements, (2) to identify the principal challenges in the managerial transformation of pesantren curricula, and (3) to formulate an integrative model of pesantren curriculum transformation that preserves classical Islamic scholarly tradition while fulfilling national education standards. Employing a systematic library research methodology drawing on thirty-three peer-reviewed sources published between 2020 and 2025, the study proposes the Pesantren Integrative Curriculum Transformation Model (PICTM), a four-pillar framework balancing tafaqquh fiddin preservation with modern curriculum management principles.